ANALISIS KADAR PROTEIN DAN LEMAK BIVALVIA (Atrina vexillum) DI PERAIRAN PANTAI DESA WAAI KECAMATAN SALAHUTU KABUPATEN MALUKU TENGAH - Alhamid, Jaffira Salma; Tuaputty, Hasan; Arini, Ine; Rehena, Johanis Fritzgal (Program Studi Pendidikan Biologi FKIP Unpatti, 2024)
bivalves are a group of invertebrate organism that are often found and live in the coastal waters of waai village. This animal has special adaptations that enable it to survive in areas that experience physical and chemical in intertidal waters. This organism also has adaptations to survive against currents and waves. However, bivalves do bnot have the ability to change location quickly so they are catch. Bivalves are marine biological resource that have high diversity. Therefore, the current level of exploitation continues to increase, so that from an ecological perspective it can threaten the sustainability of bivalves populations. Protein comes from the Greek word protos which means “most important”. Protein is one of a group of macronutrients (nutrients needed in large quantities), unlike other macronutrients, for fast, protein has a more important role in biomolecular formation than energy sources (building blocks of body shape). Fat is a molecule consisting of oxygen, hydrogen, carbon and phosphorus. Fat does not easily dissolve fat, a special fat solvent such as Choloform is needed.